Academic International Exchange In Physical Activity For People With Spinal Cord Injury: Experience Report From Mcmaster University (Revista Profissional da Associação Brasileira de Atividade Motora Adaptada, 2016)
The goal of this report is to describe the internationalacademic experience at McMaster University,Department of Kinesiology, in June, 2016, duringthe PhD. in Associate Graduate Program in PhysicalEducation UEL / UEM. McMaster University is hometo two important activities in physical activity and spinalcord injury: SCIAction Canada and MacWheelersexercise program.